Emotional Labour and the Autonomy of Dependent Self-Employed Workers: The Limitations of Digital Managerial Control in the Home Credit Sector. (August 2022) - Terry, Esme; Marks, Abigail; Dakessian, Arek; Christopoulos, Dimitris
Changes to the labour process in the home credit sector have exposed the industry's agency workforce to increased levels of digital managerial control through the introduction of lending applications and algorithmic decision-making techniques. This article highlights the heterogeneous nature of the impact of digitalisation on the labour process and worker autonomy – specifically, in terms of workers' engagement in unquantified emotional labour. By considering the limitations of digital control in relation to qualitative elements of the labour process, it becomes evident that emotional labour has the scope to be a source of autonomy for dependent self-employed workers when set against a backdrop of heightened digital control. This article therefore contributes to ongoing labour process debates surrounding digitalisation, quantified workers and digital managerial control.